HUBUNGAN PENERAPAN SISTEM MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA DENGAN MOTIVASI KERJA DAN STRES KERJA PADA PERAWAT DI RSU ANUTAPURA PALU - , LUSIA SALMAWATI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Management of work safety and health system (SMK3) should be applied in all workplaces including hospitals whose a great risk of accidents and occupational diseases. Workplace accidents that occur on health care workers are influenced by several factors. Causative factors are often due to workersâ lack of awareness and quality, inadequate skill, and low work motivation that is directly proportional to the high level of occupational stress on health workers. Objective: To analyze relationship between the application of Management of work safety and health system (SMK3) and work motivation and occupational stress. Methods: This study is a correlative research with survey method using a crosssectional design. Results: (1) The results of Pearson Product Moment Correlation show that there is very small relationship and no signifikan between the application SMK3 and work motivation (P = 0.412